2015
DOI: 10.15376/biores.10.2.2213-2222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Decorative Veneer and Structure on the Thermal Conductivity of Engineered Wood Flooring

Abstract: This paper explores the thermal conductivity of engineered wood flooring, which is widely used in world market. The effects of decorative veneer type and structure on the thermal conductivity of engineered wood flooring were studied. Four decorative veneer types and three different structures of engineered wood flooring served as test specimens. All samples were placed in a laboratory simulating a heating system environment, of which the temperature should be measured three times every five minutes. The temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
5
0
2
Order By: Relevance
“…The differences between the equilibrium temperatures of the specimens' top and bottom surfaces (Tv) are shown in Table 2. Wood-based materials showed higher Tv values than the CT, and their sequence was SW > PW > MDF > WPC, which suggested the correlation between the density and the thermal conductivity of a material (Chen et al 2015). The density of WPC could be manipulated by adjusting its recipe and processing techniques (Leu et al 2012;Prisco 2014), so that the thermal conductivity of the WPC could be designed to meet the requirements for heating floor production.…”
Section: Thermal Properties Of Heating Floor Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences between the equilibrium temperatures of the specimens' top and bottom surfaces (Tv) are shown in Table 2. Wood-based materials showed higher Tv values than the CT, and their sequence was SW > PW > MDF > WPC, which suggested the correlation between the density and the thermal conductivity of a material (Chen et al 2015). The density of WPC could be manipulated by adjusting its recipe and processing techniques (Leu et al 2012;Prisco 2014), so that the thermal conductivity of the WPC could be designed to meet the requirements for heating floor production.…”
Section: Thermal Properties Of Heating Floor Materialsmentioning
confidence: 99%
“…When the thermal properties of four different wood veneers and the floorboards of three different structures were compared, solid wood of higher density was the most suitable for indoor heating (Chen et al 2015). To improve energy-efficiency and find floor materials of better thermal conductivity, researchers using electrothermal films as a heat source have studied the thermal properties of floorboards prepared with solid wood and high density fiberboard and compared their heat transfer coefficients and heat storage properties (Seo et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The global wood flooring market, considering the main economic areas, is estimated at around 397M m 2 in China, 172M m 2 in North America, and 81M m 2 in Europe [11]. Wood engineered floorings are the largest product segment, accounting for 52%, 23%, and 82% of the market share in North America, China [12], and Europe [7,13], respectively. A growth of 5% is expected for the next 5 years, and veneer flooring will experience the highest growth, mainly concentrated in China [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…Seo et al [7] found that it was effective to increase the thermal conductivity of the wood flooring by using exfoliated graphite nanoplatelets (xGnP) or resin/xGnP composites as adhesive. Chen et al [8] studied the thermal properties of four engineered wood floors with the same structure but different decorative veneers, revealing that the higher the density, the better the thermal conductivity. In short, there were numerous studies on heat transfer with the condition of different floor heating structures [9,10].…”
Section: Introductionmentioning
confidence: 99%